STUDI ATAS PEMIKIRAN B.F. SKINNER TENTANG BELAJAR - ZAINI, RIFNON (Universitas Islam Negeri Raden Intan Lampung, 2014)
There are quite a lot of systems of theory which are constructed to examine learning problems, but it must be recognized that most of the history of learning theories are dominated by connectionist and behaviorism. Learning cannot be separated from the discussion of human nature, science, and education themselves. Many people talk about it, in this case, their conception may enrich the percepective of the learning theory itself so that it make the learning theory varied. The intense of this article is to review the concept of learning and instruction based on Skinner’s behaviorisme learning theory, and it is expected that what is discussed in this article to be implemented in an ideal education form.